Adipose-derived stem cells in ovarian cancer progression, metastasis, and chemoresistance. Issue 16 (August 2021) - Zhang, Wenjing; Torres-Rojas, Carolina; Yue, Junming; Zhu, Bing-Mei
Ovarian cancer is the deadliest gynecological malignancy due to its symptomless early stage, metastasis, and high recurrence rate. The tumor microenvironment contributes to the ovarian cancer progression, metastasis, and chemoresistance. Adipose-derived stem cell in the tumor microenvironment of ovarian cancer, as a key player, interacts with ovarian cancer cells to form the cancer-associated fibroblasts and cancer-associated adipocytes, and secretes soluble factors to activate tumor cell signaling, which can promote ovarian cancer metastasis and chemoresistance. We summarize in this review the recent progress in the studies of interactions between adipose-derived stem cell and ovarian cancer, thus, to provide some insight for ovarian cancer therapy through targeting adipose-derived stem cell.